Simulation of ant colony optimization on hole making performance - Abdullah, Haslina; Tuan Zahari, Tuan Muhammad Lutfi; Zakaria, Mohamad Shukri (2018)
Hole making operation one of machining process widely used in industrial industry. One of the main criteria in determining the efficiency of machining performance in hole making operation is shortest machining time. In this paper, simulation approach based on Ant colony optimization (ACO) has been done on hole making operation in order to minimize the machining time. The result based on ACO has been compared with the result obtain based on Genetic Algorithm (GA). Based on the simulation results, the ACO is enhance the performance of hole making process by reducing 13.5% of machining time. The results show that ACO is capable to minimize the machining time of hole making procees.